The role of intercellular adhesion molecule-1 in head and neck cancer - Georgolios, A.; Batistatou, A.; Bonitsis, N.; Stagikas, D.; Manolopoulos, L.; Charalabopoulos, K. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
The intercellular adhesion molecule-1 (ICAM-1) is a member of the immunoglobulin gene superfamily of adhesion molecules expressed in multiple human tissues and participating in various physiologic and pathophysiologic processes of the human body. The alterations in the expression of ICAM-1 in the various types of the cancer of the head and neck are discussed in this mini-review following the existing status from the current literature. Possible applications of this developing knowledge in the diagnosis and prognosis of head and neck cancer are briefly mentioned. Молекулы межклеточной адгезии (ICAM-1), являющиеся продуктом гена — члена суперсемейства генов иммуноглобулинов, экспрессированы в клетках многих тканей человека и принимают участие в ряде физиологических и патофизиологических процессов. В мини-обзоре обобщены последние данные доступной литерату ры об изменении уровня экспрессии IG4M-1 при раке головы и шеи. а также обсуждены возможности применения знаний о молекулах адгезии в области диагностики и прогноза заболевания.